2020
DOI: 10.2147/ott.s229997
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lamin B1 Overexpresses in Lung Adenocarcinoma and Promotes Proliferation in Lung Cancer Cells via AKT Pathway</p>

Abstract: These authors contributed equally to this workPurpose: This study aims to investigate the biological effect and molecular mechanism of Lamin B1(LMNB1) in lung cancer cells and its significance for the prognosis of lung adenocarcinoma(LUAD) patients. Methods: In this study, Bioinformatics was performed to analyze the expression at mRNA level and prognosis effect of LMNB1 in LUAD from TCGA dataset. The immunohistochemistry(IHC) assay was conducted to analyzed the expression of LMNB1 at the protein level in LUAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
(36 reference statements)
1
23
0
Order By: Relevance
“…7 Another study indicated that LMNB1 is significantly upregulated in lung adenocarcinoma tissues and regulates the proliferation of lung cancer cells through the AKT signaling pathway. 8 However, the biological role of LMNB2 in HCC has not been explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Another study indicated that LMNB1 is significantly upregulated in lung adenocarcinoma tissues and regulates the proliferation of lung cancer cells through the AKT signaling pathway. 8 However, the biological role of LMNB2 in HCC has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, elevated LMNB2 level has been associated with worse histological grade, advanced tumor TNM stage, and poor prognosis in non‐small cell lung cancer (NSCLC) 7 . Another study indicated that LMNB1 is significantly upregulated in lung adenocarcinoma tissues and regulates the proliferation of lung cancer cells through the AKT signaling pathway 8 . However, the biological role of LMNB2 in HCC has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The role of LMNB1 in tumor initiation and progression still remain elusive. Based on the data of TCGA, we found that LMNB1 was highly expressed in not only lung adenocarcinoma (11), prostate cancer (12,13), cervical cancer (14) and liver cancer ( 16), but also most other human cancer types. Though previous reports indicated that LMNB1 was downregulated in breast cancer by qRT-PCR (17), gastric cancer (18), lung adenocarcinoma and squamous cell carcinoma by IHC staining (19), TCGA analysis indicated LMNB1 expression in the above 4 tumor kinds was upregulated at least in the mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…Lamins are found implicated in the regulation of in a wide variety of nuclear processes, including DNA replication and repair, mitotic spindle assembly, chromosome distribution, oxidative stress response, and gene expression (5)(6)(7)(8)(9)(10). Recently, increased studies have revealed that LMNB1 is abnormally expressed in a lot of human cancer types, such as upregulated in lung adenocarcinoma (11), prostate cancer (12,13), cervical cancer (14), pancreatic cancer (15), liver cancer (16), and downregulated in breast cancer (17), gastric cancer (18) and two subtypes of lung cancer (19). Though previous evidences showed that LMNB1 expression affected the clinical behavior and patient outcome of the above cancer types, the precise mechanism underlying carcinogenesis of LMNB1 has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Lamins are found implicated in the regulation of in a wide variety of nuclear processes, including DNA replication and repair, mitotic spindle assembly, chromosome distribution, oxidative stress response, and gene expression [ 5 10 ]. Recently, increased studies have revealed that LMNB1 is abnormally expressed in a lot of human cancer types, such as upregulated in lung adenocarcinoma [ 11 ], prostate cancer [ 12 , 13 ], cervical cancer [ 14 ], pancreatic cancer [ 15 ], liver cancer [ 16 ], and downregulated in breast cancer [ 17 ], gastric cancer [ 18 ] and two subtypes of lung cancer [ 19 ]. Though previous evidences showed that LMNB1 expression affected the clinical behavior and patient outcome of the above cancer types, the precise mechanism underlying carcinogenesis of LMNB1 has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%